Non-alcoholic fatty liver disease and concomitant diseases: a differentiated approach to the prescription of antioxidants - Feysa, Сніжана (Psychosomatic Medicine and General Practice, 2019)
The relevance of work is determined by wide occurrence of non-alcoholic fatty liver disease (NAFLD) often combined with other comorbidities and ambiguity of recommendations about treatment of such patients. Studying of the combination of NAFLD and subclinical hypothyroidism (SH) is associated with wide spread of thyroid pathology in iodine deficiency endemic regions. Material and methods. There were 117 patients and 20 healthy persons (control group) examined. A complex of clinical, instrumental, and laboratory research methods was used to verify diagnoses according to the existing clinical protocols. Laboratory research of the prooxidant-antioxidant blood system was performed by using spectrophotometric methods according to the methodology developed by the Scientific Center of Radiation Medicine of the Academy of Medical Sciences of Ukraine. Results. In cases of NAFLD with concomitant pathology not only activation of lipid peroxidation (LPO) is observed, but suppression of antioxidant defense system (ADS) as well. If patients with NAFLD on the background of carbohydrate metabolism disturbances have also subclinical hypothyroidism, the LPO processes are significantly activated, and ADS is significantly depressed (compared to subclinical hypothyroidism patients), although in group of patients with isolated subclinical hypothyroidism the mean MDA level was not significantly different from healthy ones. After calculating the ADS factor of all the patients and healthy persons and ranking all of them in descending order according to their ADS factor it was discovered that the patients suffering from isolated NAFLD in the overwhelming majority had a slight suppression of ADS, which did not justify the expediency of antioxidant therapy. Instead, the patients with NAFLD and comorbid pathology were characterized by moderate and severe inhibition of ADS, which gives grounds for recommending antioxidant medicines for their treatment. Such a differentiated approach to prescribing therapy based on the antioxidant system status allows to optimize treatment and avoid polypharmacy. Conclusion. Activation of LPO and inhibition of ADS system in the patients with NAFLD were intensified on the condition of combined pathology. A differentiated approach to the prescribing of antioxidants to the patients with NAFLD was grounded: antioxidant medicines should be recommended to those ones with a comorbidity, whereas the patients with isolated NAFLD do not need antioxidant therapy in the vast majority.